The Importance of Facilities and Infrastructure Management in School - Eni Elfina; Giatman; Ernawati (Institute of Computer Science (IOCS), 2022)
This study aims to explain the importance of managing facilities and infrastructure in schools. Management of facilities and infrastructure is a factor that cannot be ignored, its existence and role as a supporting factor for the success of learning activities in schools and can improve the quality of a school. This research uses a library approach method. Library materials can be in the form of published notes, books, magazines, newspapers, manuscripts, journals or articles. The results showed that the management of infrastructure is very important in a school. This can be seen from 1) the definition of educational infrastructure, namely facilities and infrastructure that have functions and roles in achieving learning activities according to the curriculum of the education unit; 2) understanding of management of educational infrastructure, namely facilities and infrastructure are utilized and managed for the benefit of the learning process in schools: 3) management of educational facilities and infrastructure, namely a) planning, b) procurement, c) inventory, d) supervision and maintenance, e ) deletion; 4) the purpose of managing facilities and infrastructure in schools is to avoid unwanted errors and failures and to increase effectiveness and efficiency in their implementation. ; 5) the influence of educational facilities and infrastructure in schools will greatly support the success of the learning process in schools; and 6) the importance of facilities and infrastructure in schools, facilitating school management in planning and procuring and evaluating infrastructure facilities in improving the quality of school services to the community, teachers and students in particular.